EFFECTS OF PROFITABILITY, SOLVABILITY, COMPANY SIZE, AND AUDITOR’S REPUTATION ON AUDIT DELAY - Gloria Debora Lisa Susilo; Putri Aprilia Manembu; Elvis Sumanti (Jurnal Penelitian Akuntansi (JPA), 2021)
This research aims to examine the effect of profitability, solvability, company size, and auditor reputation on audit delay. Sample used in this research are banks listed on IDX from 2014-2018 and collected   by using purposive sampling methods. Data obtained from the financial report provided on IDX or company website. Results show profitability and solvability have no significant effect towards audit delay. Meanwhile, both company size and auditor reputation have a significant negative effect on audit delay. The result implies the importance of issuing certain audit regulation for banking in order to reduce audit delay.